2018
DOI: 10.1016/j.kint.2018.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Metformin prevents the development of severe chronic kidney disease and its associated mineral and bone disorder

Abstract: Chronic kidney disease (CKD) causes dysregulation of mineral metabolism, vascular calcification and renal osteodystrophy, an entity called 'CKD-Mineral and Bone Disorder' (CKD-MBD). Here we determine whether metformin, an anti-diabetic drug, exerts favorable effects on progressive, severe CKD and concomitant mineral metabolism disturbances. Rats with CKD-MBD, induced by a 0.25% adenine diet for eight weeks, were treated with 200 mg/kg/day metformin or vehicle from one week after CKD induction onward. Severe, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(54 citation statements)
references
References 40 publications
2
50
0
Order By: Relevance
“…Recent experimental data in a rat model of chronic kidney disease (CKD) showed that kidneys from the metformin group exhibited significantly less cellular infiltration, fibrosis and inflammation, and that metformin protected against the development of severe renal failure (while preserving calcium phosphorus homoeostasis) and vascular calcification. Of note, these positive effects were independent of any glucose-lowering effect in this model using non-diabetic rats [31]. Overall, these preclinical data suggest that the potential benefits of metformin on renal outcomes in patients with T2DM may well extend beyond its antihyperglycaemic activity.…”
Section: Metforminmentioning
confidence: 57%
“…Recent experimental data in a rat model of chronic kidney disease (CKD) showed that kidneys from the metformin group exhibited significantly less cellular infiltration, fibrosis and inflammation, and that metformin protected against the development of severe renal failure (while preserving calcium phosphorus homoeostasis) and vascular calcification. Of note, these positive effects were independent of any glucose-lowering effect in this model using non-diabetic rats [31]. Overall, these preclinical data suggest that the potential benefits of metformin on renal outcomes in patients with T2DM may well extend beyond its antihyperglycaemic activity.…”
Section: Metforminmentioning
confidence: 57%
“…; Neven et al. ). We have previously demonstrated that metformin can attenuate inflammation as well as tubular damage in a unilateral ureteral obstruction (UUO) model (Christensen et al.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, many additional unexpected but effective roles of metformin were found. Studies showed that metformin exerts a strong effect on numerous cancers (6,7), cardiovascular disease (CVD) (8), liver diseases (9), obesity (10), neurodegenerative diseases (11), and renal diseases (12). Sole medication or combination therapy with other drugs has shown to be effective to treat different diseases.…”
Section: Introductionmentioning
confidence: 99%